Mutation characteristics of angioimmunoblastic T-cell lymphoma: an analysis of 75 cases - Shen, X; Yi, H M; Li, A Q; Ouyang, B S; Dong, L; Wang, C F (Zhonghua bing li xue za zhi, 2024)
To investigate the characteristics of gene mutations in angioimmunoblastic T-cell lymphoma (AITL). Seventy-five AITL cases diagnosed at the Department of Pathology, Ruijin Hospital Affiliated to Shanghai Jiaotong University School of Medicine, Shanghai, China from June 2021 to June 2023 were included. Their formalin-fixed and paraffin-embedded or fresh tissues were subject to targeted next generation sequencing (NGS). The sequencing data was collected, and the distribution and type of gene mutations were analyzed. 492 potential driver mutations were identified in 74 out of the 84 genes. Targeted sequencing data for the 75 AITL patients showed that the genes with mutation frequencies of ≥10% were TET2 (89.3%), RHOA (57.3%), IDH2 (37.3%), DNMT3A (36.0%), KMT2C (21.3%), PLCG1 (12.0%), and KDM6B (10.7%). There were significant co-occurrence relationships between TET2 and RHOA, TET2 and IDH2, and RHOA and IDH2 gene mutations ( <0.05), respectively, while TET2 and KDM6B gene mutations were mutually exclusive ( <0.0